The Sifir Ajang Formula: Mathematical Precision and Cultural Heritage in Melanau Songket Weaving - Asrul Asshadi, Mohamad Morni; Rafeah, Legino; Alexander, Chelum; Laura Pranti, Tutom (2025)
This study investigates the Sifir Ajang formula, an advanced mathematical framework integral to the traditional art of Melanau songket weaving in Sarawak, Malaysia. This formula, which dictates the arrangement of threads to produce culturally significant motifs, represents the confluence of mathematical precision, artistic craftsmanship, and cultural identity. By integrating ethnomathematics and semiotic analysis, this paper examines how the Sifir Ajang formula functions both as a technical blueprint for artisans and as a living cultural artifact. The study highlights the way this formula encapsulates not only mathematical knowledge but also values, spirituality, and social narratives, thereby playing a critical role in preserving intangible cultural heritage and fostering sustainable artisanal practices.